Health professionals’ experience of treatment of patients whose community treatment order was revoked under new capacity-based mental health legislation in Norway: qualitative study - Nina Camilla Wergeland; Åshild Fause; Astrid Karine Weber; Anett Beatrix Osnes Fause; Henriette Riley (BJPsych Open, 2022)
Background Norway introduced capacity-based legislation in mental healthcare on 1 September 2017 with the aim of increasing patient autonomy and legal protection and reducing the use of coercion. The new legislation was expected to be particularly important for patients under community treatment orders (CTOs).